Rough U-Exact Sequence of Rough Groups - Ayuni, Fitri; Fitriani, Fitriani; Faisol, Ahmad (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
The notion of a U-exact sequence is a generalization of the exact sequence. In this paper, we introduce a rough U-exact sequence in a rough group in an approximation space. Furthermore, we provide the properties of the rough U-exact sequence in a rough group.